What shapes the influence evidence has on policy? The role of politics in research utilisation - Porter, C (Young Lives, 2010)
What shapes the influence evidence has on policy? The key lesson that emerges from this paper is the primacy of politics in shaping how evidence is used. In order to influence the policy process, the research community must understand both the technocratic and the political aspects of policymaking, and how these shape the choices and incentives of policy elites. The paper proposes guidelines for integrating political economy analysis into different stages of the research and communication process. It addresses three main questions: What are the assumptions behind and problems with the concept of evidence-based policy and what can be learnt from this? What prevents the effective utilisation of research in policymaking? How can we put into practice what we know about the role of politics in shaping how evidence is used? The paper draws on some examples from Young Lives, a longitudinal study of childhood poverty in Ethiopia, India, Vietnam and Peru, and contains case studies of how researchers engaged with policymakers.